Re-hierarquização e Extrapolações para o Limite do Conjunto de Base Completo - Pansini, Fernando Néspoli Nassar (2015)
A method previously suggested to calculate the correlation energy at the complete basis set limit by reassignment of the basis hierarchical numbers and use of the unified singlet- and triplet-pair extrapolation scheme is applied to a test set of 106 system. The approach is utilized to obtain extrapolated correlation energy, atomization energy, and electrical properties in the complete basis set limit with the second order MfllerPlesset perturbation theory, coupled-cluster singles and doubles excitations method, and the coupled-cluster singles and doubles excitations with perturbative triples corrections. Good agreement is obtained with the best available estimates even when the (d,t) pair of hierarchical numbers is utilized to perform the extrapolation. This conceivably justifies that there is no strong reason to exclude double-zeta energies in extrapolations, especially if the basis is calibrated to comply with the theoretical model. Furthermore, a simple unifiedsingle-parameter-extrapolation scheme is suggested to extrapolated the valence correlation energies to the complete basis set limit in species formed by atoms of H through Ne. The performance of the novel scheme is benchmarked for the correlation energy with a data set of 106 systems and, for the average polarizability, with 8 molecules. For the former, the results are excellent, most often better than when extrapolated with the best popular twoparameter protocols available in the literature. For the polarizability, the results show an enhancement relative to the raw ab initio values, and good agreement with the experimental ones.